Cost Management in Logistics of Warehousing: The Use of Activity-Based Costing in the Logistics Service Provider - Kučera, Tomáš (Scientific Research Center Ltd., 2018)
The activity-based costing method is considered as a universal management tool that applies to flow mapping and cost behaviour. The basic idea of activity-based costing is to find the true causal link between cost and performance and to display these facts in the calculation system so that the outputs are as close as possible to the reality. This method defines the structure of business processes and activities. Activity-based costing primarily focuses on improving the assignment of overhead costs, which are often allocated on a direct cost basis or direct worked hours. This method was imported to address the problems encountered by logistics service providers. The aim of this article is to use activity-based costing as a management method in a logistics service provider with regard to the cost management. The article is based on research of the world literature especially Web of Science database and Scopus database, in-depth interviews with managers that is the method of the qualitative research and an analysis of internal data of the logistics service provider. The basic advantages of qualitative research are the detailed description and insight into the study of the issue, in addition it responds well to local situations and conditions and can search for local causal connections. The article shows the possibility of using activity-based costing to better calculate the logistics costs of warehousing in a selected logistics service provider.
Řízení nákladů ve skladové logistice: aplikace metody activity-based costing u poskytovatele logistických služeb
Keywords: activity-based costing; logistics costs; logistics service provider; cost calculation; warehousing; activity-based costing; logistické náklady; poskytovatel logistických služeb; kalkulace logistických nákladů; skladování